Comparison of Different Antibody Clones for Immunohistochemistry Detection of Programmed Cell Death Ligand 1 (PD-L1) on Non–Small Cell Lung Carcinoma. Issue 2 (February 2018) - Parra, Edwin R.; Villalobos, Pamela; Mino, Barbara; Rodriguez-Canales, Jaime
Abstract : Programmed cell death ligand 1 (PD-L1) is a major immune checkpoint protein that mediates antitumor immune suppression and response. Preliminary data suggest that its detection using immunohistochemistry (IHC) in formalin-fixed and paraffin-embedded tissues may predict clinical response to PD-1/PD-L1 therapy. In diagnostic pathology, it is essential to count with a validated IHC that can reliably detect PD-L1-positive cases. The present study was conducted to compare and validate different PD-L1 commercial clones and identify which ones can be reliably used by surgical pathologist to detect PD-L1 expression in human cancer tissues. Eight commercial available PD-L1 clones were tested and compared with a noncommercial PD-L1 antibody clone 5H1. Western blot and IHC using cell lines and human tissues were used to validate these clones. From all PD-L1 antibodies, only the clones E1L3N, E1J2J, SP142, 28-8, 22C3, and SP263 passed the Western blot and IHC validation, providing similar pattern than the clone 5H1 and then they were tested in 259 non–small cell lung cancer cases placed in 9 tissue microarrays. Among all cases, only those with ≥2 cores were included (185 cases). Positive and significant correlation was found between the median PD-L1 H-score in tumor and stroma compartments, for all selected antibodies. Overall, 56 of 185 cases were detected as positive cases in malignant cells expressing membranous PD-L1 by all the clones. However, the clone SP263 identified more PD-L1-positive cases compared with the other clones. Our results show that clones E1L3N, E1J2J, SP142, 28-8, 22C3, and SP263 provide positive membrane staining pattern comparable with clone 5H1. These commercial clones are comparable, but a careful evaluation by the pathologist is necessary to minimize error of positive misinterpretations.